Fatores abióticos na biomassa, teor e qualidade do óleo essencial de manjericão - Santos, Hernandes Rufino dos (2017)
Basil was selected and improved to many different purposes, as the cooking, ornamentation and essential oil production. Basil varieties has high contents of linalool na 1,8-cineole in its composition, extracted mainly from its leaves. Brazil presents areas with great potential and specific soil and climate characteristics, which may influence in development and adaptation of the medicinal or aromatic species. Thereby, cultivation of these plants in areas with peculiar characteristics must be in the ideal patterns to each specie explored, looking for improving quality and quantity of the raw material. Before to implant a cultivation in comercial scale, becomes necessary to know the culture behavior about the biotics and abiotics effects of the region studies in essential oil has been shown important regarding the demand by natural products, once its active principles combat a serie of diseases that affect plants, animals and human. The chemical composition of the essential oil is influenced mainly by abiotic factors, that represent a interaction between the plants and the environment. Depending on the conditions, the biosynthesis of many compounds may increase or decrease, among this interactions is the competition between plants, development stage, age, nutrition, temperature, luminousity, water deficit, harvest season and time. Considering the scacity of information about the culture and its secondary compound and cultivation techniques to increase its oil essential, it was objected to investigate the stress efect by abiotic factors in basil cultivated in Cariri cearence on quantity And the content of the active principles of its essential oil, as well as in the production of biomass.